A commercial macroalgae extract in a plant-protein rich diet diminished saturated fatty acids of Oncorhynchus mykiss walbaum fillets. Issue 1 (14th December 2020) - Bruni, Leonardo; Secci, Giulia; Mancini, Simone; Faccenda, Filippo; Parisi, Giuliana
Abstract: Seaweeds are considered novel feed ingredients, nutraceutical compounds and source of pigments and proteins. They appear to possess bioactive properties, such as hypolipidemic, antioxidant and immune-stimulative actions; furthermore, their proteins are considered just as nutritious as terrestrial vegetables. In the present work, rainbow trout ( Oncorhynchus mykiss Walbaum) was fed for 95 days with three diets: a fishmeal-based positive control diet (C+), a vegetable protein-based negative control diet (C−) and a diet similar to C − where 5% of soybean concentrate was replaced by a commercial blend of seaweeds (T). The monitored parameters were fish performance, physical and marketable characteristics, fillet oxidative status and fatty acid content. The estimated indices of enzyme activities involved in lipid metabolism were calculated. Fish performances were reduced in C − and T fish; C − and T fillet fatty acid (FA) profiles globally showed the same pattern and were distinct from C+, i.e. with a lower content of polyunsaturated FAs and a higher content of monounsaturated and polyunsaturated n6 FAs; contrarywise, saturated FAs were significantly lower in T group in comparison to the other two groups ( p  < .01). The estimated indices of enzyme activity highlighted differences between dietary groups; desaturase activities of C18 and n3 FAs were higher in T in comparison to C− ( p  < .001). A slight impoverishment of antioxidant activity was found in T compared to C + group. Dietary seaweeds seemed to be capable of influencing fillet FA composition as well as the activity of enzymes related to lipid metabolism. Further studies in this regard are encouraged. Highlights: Seaweeds are novel feed ingredients with nutraceutical properties Saturated fatty acids of rainbow trout fillets were lowered by seaweed inclusion in the diet Estimated desaturase activities of C18 and n3 fatty acids were higher in seaweed-fed trout